Can You Tell Your Left From Your Right? A Role for Rab GTPases in Asymmetric Ion Transporter Localization - Morrie, Ryan David (Tufts Archival Research Center, 2005)
Externally, vertebrates display bilateral symmetry along their midline such that their left and right sides appear to be mirror images of each other. However, the internal arrangement of organs within vertebrates does not follow suit, as multiple organs are positioned asymmetrically in a consistently biased manner. Determining how asymmetry is established is important not only for the field of developmental biology but also for medical applications. Multiple models have been put forth to explain the establishment of asymmetric organ laterality. The cytoplasmic flow model, supported by pharmacological and molecular genetic data, postulates that ion transporters are positioned asymmetrically within the early embryo due to the inherent chirality of the cytoskeleton, creating a gap junction-dependent electrochemical gradient that asymmetrically localizes charged molecules such as serotonin. In this way, serotonin may be thought of as a left-right morphogen, whose biased localization leads to asymmetric downstream gene expression, distinguishing between left and right. One key question that remains for this model is how the cytoskeletal architecture is interpreted to asymmetrically localize ion transporters. Because Rab GTPases regulate nearly all aspects of membrane trafficking, we hypothesized that Rab GTPases were responsible for the directed, asymmetric shuttling of ion pumps and channels. We found that DN and WT injections of Rab11 and Rab5 randomize organ situs. In addition, we quantified the localization of ion transporters previously shown to be asymmetrically expressed, as well as some ion transporters that have not been characterized, at the 4-cell stage in Xenopus embryos. We demonstrated that the asymmetric expression of these ion transporters is dependent on proper Rab11 and Rab5 function. Co-localization of either Rab11 or Rab5 with ductin, the small c subunit of the H+-V-ATPase, further indicates that Rab11 and Rab5 could be directly controlling ion transporter localization. We propose that Rab GTPases regulate left-right asymmetry by directing the asymmetric localization of ion transporters in the early embryo along the chiral cytoskeleton.